PjBL–STEM Learning Design for Enhancing Mathematical Critical Thinking and Environmental Literacy through Plastic Waste Recycling in Elementary School - Tri Dyah Prastiti; Jackson Pasini Mairing; Dwi Sambada; Intan Fatimah Ahmadah (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Conventional mathematics instruction rarely integrates environmental sustainability themes, limiting students' opportunities to develop both mathematical reasoning and ecological awareness. Objective: This study developed and evaluated a PjBL–STEM learning design to simultaneously enhance mathematical critical thinking and environmental literacy among elementary students through plastic waste recycling projects. Methods: Using the 4-D R&D model followed by a quasi-experimental nonequivalent control group design, 32 elementary students selected via purposive sampling participated. Instruments were validated through expert judgment (Cronbach's α = 0.87). Data were analyzed using an independent samples t-test after normality and homogeneity tests (α= 0.05). Results: The PjBL–STEM model significantly improved students' critical thinking (t = 4.32, p < 0.05). Post-test mean scores of the experimental group (M = 91.25, SD = 5.84) significantly exceeded those of the control group (M = 74.50, SD= 8.21). Students demonstrated strong performance across all five critical thinking indicators. Conclusion: PjBL–STEM learning effectively integrates mathematical critical thinking and environmental literacy, offering a reproducible interdisciplinary model for sustainability-oriented mathematics education.